Feasibility Of Tensile Membrane Structure In Ahmednagar City - Hrushikesh vivek khose; Anand Niranjan Gholap; Abdullah Asfaq Hussain; Prajakta Ganeshdip Chemate (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Membrane structures are hugely popular in the rapidly developing world of civil engineering and there use is increasing in different aspects of buildings. There is an increasing trend concerning the use of membrane structures within architectural design for better aesthetical view and better alternative for traditional roofing materials. It is important to recognize the reasoning behind the growth in popularity. The implementation of these new technique needs to be boosted in Ahmednagar city as there are very few practical applications at present. This paper contains the survey of the city for the locations where these structures can be assembled. Market survey is also mentioned to ultimately check that is a tensile membrane structure really feasible in current scenario of Ahmednagar district.